Uji Kualitas Air Mineral Kemasan dan Pemurnian Air Menggunakan Lempung Aktif - Narto BE; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2008)
Thirty seven samples of bottled mineral water of 15 existing brands from Yogyakarta’s surrounding areas had been analysed. The analysis used Atomic Absorption Spectrophotometric and Spectrometric methods, and were aimed to examine metal and anion contents. In general, the results of the analysis showed that mineral content in bottled water samples has fulfilled the Indonesian Industry Standard. However, still few of them disconformed the contents stated on their corresponding labels. In order to produce high quality bottled water, the usefulness of activated clay as ion exchange resin was subsequently tested. The test showed that activated clay can be used as purifier media for processing river water or industrial waste water to generate mineral drinking water.